Profiling the inhibitory receptors LAG-3, TIM-3, and TIGIT in renal cell carcinoma reveals malignancy - Kimiharu Takamatsu (Nature Portfolio, 2021)
Targeting the inhibitory receptors (IRs) LAG-3, TIM-3 and TIGIT is a promising immune-oncology approach and the identification of biomarkers of response is crucial. Here, the authors apply automated single-cell count for these IRs in human renal cell carcinoma and investigate the immunogenomic landscape of the disease.